2021
DOI: 10.1093/bbb/zbab106
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and saponins in plant rhizospheres: roles, dynamics, and the potential for agriculture

Abstract: Plants are in constant interaction with a myriad of soil microorganisms in the rhizosphere, an area of soil in close contact with plant roots. Recent research has highlighted the importance of plant specialized metabolites (PSMs) in shaping and modulating the rhizosphere microbiota; however, the molecular mechanisms underlying the establishment and function of the microbiota mostly remain unaddressed. Flavonoids and saponins are a group of PSMs whose biosynthetic pathways have largely been revealed. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 163 publications
0
15
0
Order By: Relevance
“…It is worth noting that DEGs of soybean roots after treatment with Fe-based NMs were mainly enriched in the pathway involved in “phenylpropanoid biosynthesis”, “flavonoid biosynthesis”, and “ATP-binding cassette (ABC) transporters” (Figure S10c-d). ABC transporters mediate the secretion of flavonoids into the rhizosphere . These altered pathways could increase flavonoid contents in roots and release them to the rhizosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that DEGs of soybean roots after treatment with Fe-based NMs were mainly enriched in the pathway involved in “phenylpropanoid biosynthesis”, “flavonoid biosynthesis”, and “ATP-binding cassette (ABC) transporters” (Figure S10c-d). ABC transporters mediate the secretion of flavonoids into the rhizosphere . These altered pathways could increase flavonoid contents in roots and release them to the rhizosphere.…”
Section: Resultsmentioning
confidence: 99%
“…ABC transporters mediate the secretion of flavonoids into the rhizosphere. 56 These altered pathways could increase flavonoid contents in roots and release them to the rhizosphere. Besides, "carbohydrate metabolism" was observed in roots after Fe-based NMs treatment, which might be due to the improved photosynthesis (chlorophyll content and Pn) by Fe-based NMs (Figure S10c,d, Figure S1b, Figure 1b), sustainably supplying the carbohydrate and energy for symbiosis and nodule formation.…”
Section: Resultsmentioning
confidence: 99%
“…Phenylobacterium , Amycolatopsis , Sediminibacterium , and Ochrobactrum were the predominant taxa correlated with tea saponin degradation in the gut of the camellia weevil [ 67 ]. However, bacteria capable of metabolizing aglycones were not isolated from soils, and the saponin catabolic pathway in bacteria remains unclear, especially in the rhizosphere [ 34 ]. To elucidate the saponin metabolism and its significance in microbiome formation, it is necessary to isolate bacterial strains belonging to taxa enriched by saponin treatments and to investigate their abilities to assimilate saponins and colonize the rhizosphere of saponin-producing plants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that saponins are secreted from plant roots into the rhizosphere [ 31 , 32 , 33 , 34 ]. Previously, we demonstrated that soyasaponins and α-tomatine were secreted from soybean and tomato roots in both hydroponic and field conditions [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A deeper understanding of the mechanisms involved in beneficial plant-bacteria interactions mediated by flavonoids may be crucial in implementing sustainable strategies aimed at increasing plant growth and productivity [36], accelerating phyto-rhizoremediation [218], improving plant protection from pathogens and, more generally, the holobiont resistance to stresses [219].…”
Section: Flavonoid Exudation Affects the Structure And Function Of Ro...mentioning
confidence: 99%